Iron Age Fibulae in the Museum of Şanlıurfa - Laflı, Ergün; Buora, Maurizio (Folia Orientalia, 2026)
In this brief article five bronze fibulae, being exposed in the museum of Şanlıurfa and belonging to the Iron Age, will be presented. At least two of these five were found at Lidar Höyük.